Literature Review: Effect of Acupressure on Point L14 During Labour - Rosidah Solihah; Rifa Aulia Aripiani; Ai Ratnaningsih (Genius Midwifery Journal, 2022)
Introduction: Labor is crucial time that causes women to experience pain due to contractions. As many as 91.9% of women experience pain during labour, especially during the first stage of the active phase. Pain can be reduced by pharmacological and non pharmacological. Non pharmacological one of which is acupressure on point L14. Acupressure is one of the non-pharmacological methods that can be used during the delivery process. Acupressure points associated with labour pain include Hegu (L14), Zhiyin (BL 67), Kunlun (BL 60), Neiguan (PC 60), Sanyinjio (SP 6), Tianjin (GB 21), Dansu (BL19) points. Aim: This literature review uses the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Results: L14 point can stimulate the production of oxytocin from the pituitary gland so that it stimulates uterine contractions to increase the labour process. Thus, in addition to reducing acupressure pain at the L14 point, it can also accelerate the first stage of the labour process. Conclusion: Acuppressure at the L14 point is proven to be effective in reducing pain and speeding up the labor process.